The Effectiveness of Environmental Education Learning Strategy Teaching Materials (SPPLH) in Improving Teachers' Cognitive Flexibility - Irah Kasirah; Nadiroh; Hafid Abbas (Jurnal Penelitian dan Pengembangan Pendidikan, 2022)
This study aims to determine the effectiveness of Environmental Education Learning Strategy (SPPLH) teaching materials in increasing the cognitive flexibility of teachers. The method used in this research is the research and development method. This study uses a quantitative approach. The place of research was carried out at SLBN 7 Jakarta. The time of study was carried out from March 2020 to October 2020. The sampling technique was carried out by Random Sampling. Product study this packed in form SPPLH teaching materials as unique references in science _ with notice characteristics of SLBN 7 Jakarta teachers. The results showed that based on the results of the t-test, Cognitive Flexibility t-test 4.42 > t table 2,042. There is a very significant difference between cognitive flexibility scores who were given SPPLH teaching materials, where the score of post-pre-test t treatment was 19.68 higher than teachers who were not given SPPLH teaching materials, namely the post-pre test score control of 9.12. Based on the results of the analysis, the SPPLH. The teaching materials model effectively boosts the teacher's cognitive flexibility in an innovative learning integrated environment.